Pengaruh Tingkat Kepedulian Sosial, Kepercayaan Donatur, Literasi Zakat, Kualitas Pelayanan Dan Akuntabilitas Terhadap Keputusan Berdonasi Di UPZ Bakti Bersama Dengan Religiusitas Sebagai Variabel Moderasi - Ahmad Najir; Nuril Huda; Siti Aliyah Al Bushairi; RR Yulianti Prihatiningrum; Marhusin (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: This study aims to: (1) determine and analyze the partial influence of the level of social concern, donor trust, zakat literacy, service quality and accountability on the decision to donate at UPZ Bakti Bersama; (2) determine and analyze the moderation of religiosity in the relationship between social concern, donor trust and zakat literacy on the decision to donate at UPZ Bakti Bersama. This study uses a quantitative method. The respondents in this study were 392 people from South Kalimantan who had distributed ZIS through UPZ Bakti Bersama. The sampling technique used was purposive sampling. The data collection technique used a questionnaire, the results of which were processed using SmartPls 4.1. The results of this study indicate that the level of social concern has a positive and significant effect on the decision to donate. Donor trust has a positive and significant effect on the decision to donate. Zakat literacy has a positive and significant effect on the decision to donate. Service quality has a positive and significant effect on the decision to donate. Accountability has a positive and significant effect on the decision to donate. Religiosity does not moderate the influence of the level of social concern on the decision to donate. Religiosity moderates the influence of donor trust on the decision to donate. Religiosity does not moderate the influence of zakat literacy on the decision to donate